Distributed Latency Profiling through Critical Path Tracing: CPT can provide actionable and precise latency analysis. - EATON, BRIAN; STEWART, JEFF; TEDESCO, JON; TAS, N. CIHAN (Communications of the ACM, 2023)
This article details the concept of critical path tracing to analyze latency in complex distributed systems. Critical path tracing works by compiling a list of the steps responsible for the slowest path of request processing and then optimizing those steps to reduce latency overall. Topics include remote procedure call or RPC telemetry, central process unit of CPU profiler analysis, and distributed tracing analysis. A detailed look at how critical path tracing works is included.